PENERAPAN METODE COOPERATIVE SCRIPT DALAM MENINGKATKAN HAFALAN SISWA MATERI SURAH ASY-SYAMS PADA MATA PELAJARAN AL-QUR’AN HADITS KELAS VII MTs AMALIYAH TANJUNG TIGA SECANGGANG - Nurul Hasanah (ANDRAGOGI, 2022)
Cooperative Script Learning Metodh is a variable used to improve students mastery in memorizing verses of the Qur’an for class VII MTs Amaliyah Tanjung Tiga, Secanggang. The subjects used in this study amounted to 39 people. The search was conducted in two cycles with each cycle having four stages, namely planning, action, observation, and reflection. Based on the result of the data in the firs cycle obtained an avarege value of 68,71% with 16 students complete (41%) and 23 students did not complete (59%). Because the avarege was not sufficient in accordance with the objectives, the research continued on the second cycle stage and obtained an avarege of 73,43% with 28 (80%) students completed and 11 930%) did not completed. Thus, it can be concluded that the metodh of memorizing the book can improve students mastery of memorizing the material of surah Asy-Syams in the subjects of Al-Qur’an hadith for class VII MTs Amaliyah Tanjung Tiga Secanggang, Langkat Regency, North Sumatra.